Teknologisk kartlegging av norsk polykrom treskulptur fra perioden 1100-1350: Nytt lys på Madonna fra Veldre, Madonna fra Østsinni og Krusifiks fra Tretten - Kollandsrud, Kaja (Hikuin, 2018)
Technological mapping of Norwegian polychrome wooden sculpture 1100-1350 New light on the Virgin from Veldre, the Virgin from Østsinni and the Crucifix from Tretten By Kaja Kollandsrud The work presented herein is part of an ongoing research project mapping the material and techniques used in the construction and painting of Norwegian polychrome wooden sculptures from the period 1100-1350. The project is presented with updated statistical figures from Kollandsrud 2002. New analysis of the Virgin from Veldre, the Virgin from Østsinni and the Crucifix from Tretten (Fig. 1-5) has revealed that these pieces have been partly re-carved and re-polychromed after their original production. The original sculptures have been dated stylistically from their carvings to different parts of the thirteenth century. The sculptures all belongs to the area around the bishopric of Hamar. Even though the original carvings are dated differently, the author suggests that the same hand could have carried out the re-painting, at least on the two Virgins. There are striking similarities between the polychrome on the three pieces. The author suggests that what is seen today is a fifteenth century alteration of an earlier scheme. This conclusion is based on the examination of the techniques and materials used and their methods of application. Other sculptures in the Oslo University collection are used as comparative examples.